Strategi Pengembangan Usaha Kecil Menengah Sektor Industri Pengolahan - Arief Rahmana (Jurnal Teknik Industri, 2012)
The paradigm underlying this research is that SME has contribution to economic growth, that is indicated by their contribution to employment and Gross Domestic Product. SMEs contribute to employment more than 99,7 per cent of national employment and contribute to more IDR 1,013.5 trillion or 56,73 per cent. Nevertheless, the developing of SME's facing some problems namely lack of capital, difficulties in marketing, simple organizational structure with unstandard job description, low of quality management, limited human resource, generally it has no finanacial accounting, low of legality aspect, and low of technology quality. According to this matter, a comprehensive strategy for developing SME's is very crusial to develop in order to fasten SME's growth, to eliminate SME's problems, and to make SME's competitive. The strategy composed based on integration of location quotient, diamond cluster model, and SWOT analysis approach. The result indicated that SME's which have big potential to develop are manufacturing industry sector, because it has the biggest value of LQ is about 4,277. Then, strategy for developing SME's is ST strategy, namely using some strength to overcome some threats. According to this strategy, SME's should carry out product diversification by using CNC, CAD, and CAM technology, improve quality of product, and cooperate with suppliers to get supply raw material.